Clinicopathologic and Prognostic Features of Pediatric Follicular Cell–derived Thyroid Carcinomas: A Retrospective Study of 222 Patients. (29th December 2022) - Saliba, Maelle; Alzumaili, Bayan A.; Katabi, Nora; Dogan, Snjezana; Tuttle, Robert M.; Zoltan, Antal; Pandit-Taskar, Neeta; Xu, Bin; Ghossein, Ronald A.
Abstract : Pediatric thyroid carcinomas (TCs) are rare and mainly approached based on data extrapolated from adults. We retrospectively reviewed 222 pediatric TCs (patient age less than or equal to 21 y). Lymph node (LN) disease volume at presentation was considered high if the largest positive LN measured ≥1 cm and/or >5 LNs were positive. High-grade follicular cell–derived thyroid carcinoma (HGFCTC) were defined by the presence of marked mitotic count and/or tumor necrosis and considered as high-risk histology along with papillary thyroid carcinomas (PTC) diffuse sclerosing variant (DSV). Disease-free survival (DFS) was analyzed. LN involvement at presentation was significantly associated with male sex, larger tumor size, lymphatic invasion, positive surgical margins, and distant metastases at presentation. Five- and 10-year DFS was 84% and 77%, respectively. Only 1 patient with HGFCTC died of disease. Within PTC variants, PTC-DSV was associated with adverse histopathologic parameters and higher regional disease spread, unlike PTC tall cell variant which did not portend worse behavior. The presence of necrosis conferred worse DFS ( P =0.006), while increased mitotic activity did not. While the entire HGFCTC group did not correlate with outcome ( P =0.071), HGFCTC with necrosis imparted worse DFS ( P =0.006). When restricted to PTC-DSV and HGFCTC with necrosis, high-risk histologic classification emerged as an independent prognostic parameter of DFS ( P =0.020). The excellent prognosis of pediatric TCs differs from that of adult TCs showing similar histologic features. While neither increased mitotic activity nor PTC tall cell variant histology predict adverse outcome, PTC-DSV and tumors with necrosis constitute high-risk histologic variants with an increased risk of protracted disease.